Robust Detection of Point Correspondences in Stereo Images - A. Stojanovic; M. Unger (Acta Polytechnica, 2007)
A major challenge in 3D reconstruction is the computation of the fundamental matrix. Automatic computation from uncalibrated image pairs is performed from point correspondences. Due to imprecision and wrong correspondences, only an approximation of the true fundamental matrix can be computed. The quality of the fundamental matrix strongly depends on the location and number of point correspondences.Furthermore, the fundamental matrix is the only geometric constraint between two uncalibrated views, and hence it can be used for the detection of wrong point correspondences. This property is used by current algorithms like RANSAC, which computes the fundamental matrix from a restricted set of point correspondences. In most cases, not only wrong correspondences are disregarded, but also correct ones, which is due to the criterion used to eliminate outliers. In this context, a new criterion preserving a maximum of correct correspondences would be useful.In this paper we introduce a novel criterion for outlier elimination based on a probabilistic approach. The enhanced set of correspondences may be important for further computation towards a 3D reconstruction of the scene.